Eksplorasi Efektivitas Mahasiswa Program Studi Pendidikan Bahasa Inggris Dalam Pembelajaran Speaking - Muhamad, Sariwati; Nasir, Vebiyanti (Peneliti.net, 2025)
The purpose of this study was to determine the desired effectiveness of students in learning speaking. This research was conducted in the English Language Education Study Program at Bumi Hijrah Tidore University, located in Akekolano Village, North Oba District, Tidore Islands City. Participants were 12 English Language Education students: 8 in their third semester, 2 in their fifth semester, and 2 in their seventh semester. The research employed a descriptive qualitative method. To obtain data, the researcher utilized observation and interviews. Observations were conducted to determine the learning situation and conditions, while interviews were conducted to address the researcher's research questions. The interview results indicated that English Language Education students can learn speaking effectively if supported by the following: using real-life communication methods, applying the principle of Fluency Before Accuracy, using a collaborative and interactional approach, providing effective and constructive feedback, a psychologically safe learning environment, and developing vocabulary.